Application of Ball Modifications in Basketball Dribble Learning on Student Motivation at SD Negeri Medaeng II Sidoarjo - Puspitasari, Yeni; Sudarso, Sudarso (Jurnal Pendidikan Jasmani (JPJ), 2024)
PJOK learning is one of the subjects in schools, which in practice requires a pleasant atmosphere with the aim of improving students physical fitness. To create a pleasant learning atmosphere, it is necessary to have a motivational boost that can build the enthusiasm of students to do PJOK learning. One of the things that can be done is to provide several games using modified sports equipment in learning to dribble basketball. By using a modified rubber ball in basketball dribble learning it can maximize and make learning time more efficient. This study aims to determine the amount of increased motivation of students using a modified rubber ball in basketball dribble learning. Using a quantitative descriptive experimental method, the population in this study was 77 students in class 5 at SDN Medaeng II using cluster random sampling technique. Based on this research, it can be concluded that there is an increase in students motivation in learning to dribble basketball using a modified rubber ball. These results were obtained from the results of filling out the questionnaire and processing the data using SPSS version 26 tools. The sig T-test result of 0.000 indicates that there is a significant difference between the results of the pretest and posttest questionnaires, as well as the results of increasing student motivation by 42.86%.